Conhecimento de estudantes de Gastronomia acerca da doença celíaca - Vanessa Silva Freitas; Martha Luisa Machado; Andréia Gonçalves Giaretta; Caroline Camila Moreira (Universidade do Estado do Rio de Janeiro, 2020)
Objective: To evaluate the knowledge of Gastronomy students about celiac disease. Methods: This is a descriptive study conducted with students from a Technology in Gastronomy course in Dourados, Mato Grosso do Sul, Brazil. Data collection was carried out in April 2019 through the application of a questionnaire organized in three sections with open and closed questions: (1) Sociodemographic issues; (2) Knowledge about celiac disease and gluten-free diet and (3) Knowledge about special care in culinary preparations for people with celiac disease. Results: Sixty students with an average age of 31.5 years old participated, most of them female (70%) and self-declared white (73.3%). Most of them have heard of celiac disease and gluten (61.7% and 100%, respectively) although the majority (66.1%) answered wrongly or was not able to answer about the concept of celiac disease. Only 15.5% believed that gluten is a protein. Only 24.5% of students correctly mentioned all the gluten-containing cereals and 5.4% correctly indicated all options to replace them. Although most of the students reported converging special care practices in gluten-free preparations, a significant number of students were wrong or not able to answer about sharing oil, utensils, and equipment for gluten and gluten-free foods (31.6% and 41.7% respectively). Approximately one-third of the students (31.6%) did not consider it necessary to verify the presence of gluten on food labels. Conclusion: The Gastronomy students present unsatisfactory knowledge about celiac disease, gluten-free diet, and culinary practices to prevent cross-contamination by gluten, which may affect the future quality of food services provided by these professionals and, consequently, in the quality of life of celiac consumers. The findings indicate the need to reform the curriculum and create curricular guidelines for Technology in Gastronomy courses in Brazil.